Carrageenan-Free Diet Shows Improved Glucose Tolerance and Insulin Signaling in Prediabetes: A Randomized, Pilot Clinical Trial - Leo Feferman; Sumit Bhattacharyya; Erin Oates; Nicole Haggerty; Tianxiu Wang; Krista Varady; Joanne K. Tobacman (Journal of Diabetes Research)
Objectives. Carrageenan is well known to cause inflammation and is used in laboratory experiments to study mediators and treatments of inflammation. However, carrageenan is added to hundreds of processed foods to improve texture. Previous work indicated that low concentrations of carrageenan in drinking water caused marked glucose intolerance and insulin resistance in a mouse model. This exploratory, clinical study tested the impact of the no-carrageenan diet in prediabetes. Research Design and Methods. Participants with prediabetes (n=13), defined as HbA1c of 5.7%-6.4%, enrolled in a 12-week, randomized, parallel-arm, feeding trial. One group (n=8) was provided all meals and snacks with no carrageenan. A second group (n=5) received a similar diet with equivalent content of protein, fat, and carbohydrate, but with carrageenan. Blood samples were collected at baseline and during oral glucose tolerance tests at 6 and 12 weeks. The primary outcome measure was changed in %HbA1c between baseline and 12 weeks. Statistical analysis included paired and unpaired t-tests, correlations, and 2×2 ANOVAs. Results. Subjects on no carrageenan had declines in HbA1c and HOMA-IR (p=0.006, p=0.026; paired t-test, two tailed). They had increases in C-peptide (p=0.029) and Matsuda Index (2.1±0.7 to 4.8±2.3; p=0.052) and declines in serum IL-8, serum galectin-3, and neutrophil phospho-(Ser307/312)-IRS1 (p=0.049, p=0.003, and p=0.006; paired t-tests, two tailed). Subjects on the diet with carrageenan had no significant changes in these parameters. Significant differences between no-carrageenan and carrageenan-containing diet groups for changes from baseline to 12 weeks occurred in C-peptide, phospho-Ser-IRS1, phospho-AKT1, and mononuclear cell arylsulfatase B (p=0.007, p=0.038, p=0.0012, and p=0.0008; 2×2 ANOVA). Significant correlations were evident between several of the variables. Conclusions. Findings indicate improvement in HbA1c and HOMA-IR in participants on no-carrageenan diets, but not in participants on carrageenan-containing diets. Significant differences between groups suggest that removing carrageenan may improve insulin signaling and glucose tolerance. Larger studies are needed to further consider the impact of carrageenan on development of diabetes.